Factors associated with cognitive impairment in Latin American older adults: A cross-sectional observational study of COVID-19 confinement - Ramos Henderson, Miguel (2023)
INTRODUCTION: The effects of COVID-19 confinement have been severe, especially in older adults. Therefore, we analyzed the factors associated with cognitive impairment (CI) in Latin America (LA). METHODS: We conducted a cross-sectional observational study with a total of 5245 older adults from 10 countries in LA. Measurement: We used the Telephone Montreal Cognitive Assessment (T-MoCA) and the Eight-item Informant Interview to Differentiate Aging and Dementia (AD8) scale. RESULTS: We found that age, depressive symptomatology, bone fractures, being widowed, having a family member with dementia, and unemployment were associated with an increased risk of CI. In contrast, higher education, hypertension with continuous treatment, quarantine, and keeping stimulating cognitive and physical activities were associated with a lower probability of CI. No significant association was found between suffering from diabetes or being retired and CI. DISCUSSION: It is essential to conduct follow-up studies on these factors, considering their relationship with CI and the duration of confinement.